The long shadow of violence: The impact of exposure to intimate partner violence in infancy and early childhood. (26th August 2020) - Mueller, Isabelle; Tronick, Ed
Abstract: Early exposure to adversities, such as witnessing intimate partner violence (IPV) can have long‐lasting impact on infants behavioral, emotional, and neurological development. Yet, research so far has focused on how IPV affects the well‐being of women or on the retrospective effects in older children. The first 2 years of life are characterized by rapid development of brain and behavior, making infants even more vulnerable than women or older children to the detrimental effects of exposure to violence. The goal of this review is to summarize the scientific findings on the effects of IPV on infant brain maturation and related socioemotional development. We describe effects of violence on attachment, symptoms of trauma in infants, and possible pathways involved in how IPV exposure may affect maturation of brain regions related to emotional regulation. We relate affected brain structures to development of stress reactivity (amygdala), memory (hippocampus), the processing of witnessed events itself (auditory and visual cortex), and how these consequences relate to potential subsequent psychopathology.